2008
DOI: 10.1016/j.neurobiolaging.2006.12.018
|View full text |Cite
|
Sign up to set email alerts
|

A non-toxic ligand for voxel-based MRI analysis of plaques in AD transgenic mice

Abstract: Amyloid plaques are a characteristic feature in Alzheimer's disease (AD). A novel non-toxic contrast agent is presented, Gd-DTPA-K6A␤1-30, which is homologous to A␤, and allows plaque detection in vivo. MRI was performed on AD model mice and controls prior to and following intracarotid injection with Gd-DTPA-K6A␤1-30 in mannitol solution, to transiently open the blood-brain barrier. A gradient echo T2 * -weighted sequence was used to provide 100 m isotropic resolution with imaging times of 115 min. The scans w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 52 publications
0
71
0
Order By: Relevance
“…This is unlikely in our study, because we did not use an extremely high resolution in MRI (100 m versus ϳ50 to 60 m; Jack et al, 2004;Lee et al, 2004;Zhang et al, 2004) as is required for potential interference by A␤ plaques. Sigurdsson et al (2008) have shown that very large plaque deposits are detectable in aged Tg2576 mice via T2*-weighted MRI at 100-m resolution. However, given the size of the plaques detected by Congo red in our work (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is unlikely in our study, because we did not use an extremely high resolution in MRI (100 m versus ϳ50 to 60 m; Jack et al, 2004;Lee et al, 2004;Zhang et al, 2004) as is required for potential interference by A␤ plaques. Sigurdsson et al (2008) have shown that very large plaque deposits are detectable in aged Tg2576 mice via T2*-weighted MRI at 100-m resolution. However, given the size of the plaques detected by Congo red in our work (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The brains were then placed overnight in a phosphate buffer solution containing 20% glycerol and 2% DMSO, and subsequently serial coronal 40 m sections of the brain were prepared and subject to fluorescent microscopy. Our previous experience with developing peptidic ligands for magnetic resonance imaging of amyloid plaques indicates that identical method of intracarotid injection, without the use of an osmotic agent, does not disrupt the blood-brain barrier (Wadghiri et al, 2003;Sigurdsson et al, 2007). Work by others supports this observation (for review, see Rapoport, 2000).…”
Section: Intracarotid Injection Of Fitc-labeled Antibodiesmentioning
confidence: 95%
“…These factors may hinder application of USPIO-Ab1-42 in future clinical trials. The authors have introduced a new nano formulation using a less toxic fragment of Ab peptide [23] and co-linking with polyethylene glycol (PEG) to replace co-injection of mannitol [24]. The Ab peptide and PEG require a special chemical linker (EDC/NHS) to attach to the USPIO surface.…”
Section: Introductionmentioning
confidence: 99%